Promoting Tropicana Slim Products to Cafés in Surabaya Using a Marketing Booklet - Clarita Ivone Rumimpunu (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
This is a Final Project report on a problem at PT. Nutrifood Indonesia. Tropicana Slim (TS) is a range of sugar free, low fat, low salt and low-calorie products. There are various ranges of TS products that can be used in Cafés, but most of the decision makers do not know that TS has other products besides sweetener. Thus, in order to introduce other products to the decision maker, a marketing tool is needed to give detail information about the products. A marketing booklet is a small book containing information about things for marketing purposes. The contents consist of general information about the company, products description, benefits of the products and contact person. To persuade the readers, Tropicana Slim’s Unique Strength Points (USP) will be emphasized in the marketing booklet contents. Thus, it will help to introduce Tropicana Slim market and penetrate its various products to the Cafés. Keywords: marketing tool, marketing booklet, USP